Transforming Lives Through Mixed Farming Systems - Ahmed, Sharif; Miajy, Abdullah; Humaira Sadaf, Bushra; Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2024)
This documentary showcases the CGIAR Research Initiative on Mixed Farming Systems, an effort implemented from 2022 to 2024 aimed at integrating crop, livestock, fishery, and agroforestry components of agriculture to enhance sustainable intensification of the mixed farming systems, the initiative has directly impacted 10,000 farmers in the northern and southern regions of Bangladesh.